Efektivitas Modul Pembelajaran IPA Berbasis Etnosains Dalam Meningkatkan Aspek Sikap Sains - S, Fitriya; Maiyanti, Aziza Anggi; Syamsudin, Hamzah Ahmad (Penerbit Widina, Widina Media Utama, 2025)
This study aims to examine the effectiveness of ethnoscience-based science learning modules in enhancing students' scientific attitudes. The primary issue addressed is the low level of scientific literacy in Indonesia, which affects students' conceptual understanding and critical thinking skills. This research employs a one-group pretest-posttest experimental design with a sample of seventh-grade students from a junior high school in Kediri. The developed module integrates local wisdom into the material on additives and addictive substances, enabling students to connect scientific concepts with their daily experiences. The conceptual framework of this study is based on scientific literacy and constructivist theory. The findings indicate a significant improvement in students' scientific attitudes after the learning intervention, with percentage increases as follows: ability to explain scientific phenomena (92.38%), data interpretation (91.90%), evaluation and design of scientific investigations (92.38%), argumentation based on scientific evidence (94.05%), and understanding the context of science in society (92.38%). The implications of this study suggest that the ethnoscience-based approach is effective in improving students' scientific literacy and can serve as an alternative strategy for developing science curricula in schools.ABSTRAKPenelitian ini bertujuan untuk mengkaji efektivitas modul pembelajaran IPA berbasis etnosains dalam meningkatkan aspek sikap sains siswa. Permasalahan utama yang diangkat adalah rendahnya literasi sains di Indonesia, yang berdampak pada kurangnya pemahaman konsep dan keterampilan berpikir kritis siswa. Penelitian ini menggunakan desain eksperimen one-group pretest-posttest dengan sampel siswa kelas VII di salah satu SMP di Kediri. Modul yang dikembangkan mengintegrasikan kearifan lokal ke dalam materi zat aditif dan adiktif, sehingga siswa dapat menghubungkan konsep ilmiah dengan pengalaman sehari-hari. Kerangka konsep penelitian ini mengacu pada literasi sains dan teori konstruktivisme. Hasil penelitian menunjukkan peningkatan signifikan dalam aspek sikap sains siswa setelah pembelajaran, dengan persentase peningkatan: kemampuan menjelaskan fenomena ilmiah (92,38%), interpretasi data (91,90%), evaluasi dan perancangan investigasi ilmiah (92,38%), pembuatan argumen berbasis bukti (94,05%), serta pemahaman konteks sains dalam masyarakat (92,38%). Implikasi penelitian ini menunjukkan bahwa pendekatan etnosains efektif dalam meningkatkan literasi sains siswa dan dapat dijadikan alternatif dalam pengembangan kurikulum pembelajaran IPA di sekolah.